Effects of malachite green treatment regimes on red tilapia (Oreochromis hybrid) and its withdrawal period - Kwan, Penz Penz (2019)
United Nations reported that the world’s average per capita consumption of fish exceeded 20 kg in year 2016. To meet the demand, many farms culture fish intensively which induces stress and increases fish susceptibility to diseases. In order to prevent the occurrence of diseases, the application of chemicals such as malachite green (MG) as a prophylactic treatment has become a common practice in some countries. However, the use of MG is strictly prohibited in fish for human consumption by the European Union and US Food and Drug Administration due to its potential carcinogenic and genotoxic properties. In spite of its health hazard, recent findings indicate the presence of MG and its metabolite, leucomalachite green (LMG) residues in many fish samples from all over the world and are of concern to human health due to the fact that consumption of fish is high in many countries. Therefore, this research examined the toxicity and accumulation of MG residues in red tilapia (Oreochromis hybrid) which is one of the highly consumed freshwater fish species in Malaysia. A sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was used to test the residues of MG and LMG which was validated using red tilapia fish muscle. A simplified method without the use of solid phase extraction for sample preparation was used. The decision limit and detection capability for MG were 0.05 µg/L and 0.09 µg/L and LMG were 0.05 µg/L and 0.08 µg/L. Acute toxicity bioassay was performed, and based on the 96 h LC50 result which was 1.06 mg/L, red tilapia were exposed to the acute, sub-acute and sub-lethal concentration of MG. Subsequently, growth parameters, blood chemistry, antioxidant status and oxidative stress were measured. Furthermore, the withdrawal period of MG after exposure to different treatment regimes was determined. Red tilapia exposed to long-term bath showed the highest accumulation of total MG and LMG residues (441.38 µg/kg) immediately after treatment in comparison to dip (once), dips (once for 5 days), short-term bath (once) and short-term bath (once for 5 days). After 30 days, sum residues of MG and LMG were 13.30 µg/L for long- term bath, whereas, for all other treatments it was below 0.26 µg/kg. In addition, MG and LMG residues in muscle tissue of commonly consumed fish such as red tilapia (Oreochromis hybrid), African catfish (Clarias gariepinus), Asian seabass (Lates calcarifer), hybrid grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and striped catfish (Pangasius hypophthalmus) were quantitatively analysed using LC- MS/MS. The fish were purchased from 11 different markets in the state of Selangor, Malaysia. Results showed that sum residues of MG and LMG ranged from 0.53 to 4.10 µg/kg, with the highest residue detected in domestic striped catfish. This study indicates that MG is still being used and aquaculture stakeholders should be made aware of the judicious use of MG for the benefit of public health.